γδ T Cells Support Pancreatic Oncogenesis by Restraining αβ T Cell Activation - Daley, Donnele; Zambirinis, Constantinos Pantelis; Seifert, Lena; Akkad, Neha; Mohan, Navyatha; Werba, Gregor; Barilla, Rocky; Torres-Hernandez, Alejandro; Hundeyin, Mautin; Mani, Vishnu Raj Kumar; Avanzi, Antonina; Tippens, Daniel; et al. (Cell, 2016)
Inflammation is paramount in pancreatic oncogenesis. We identified a uniquely activated γδT cell population, which constituted ∼40% of tumor-infiltrating T cells in human pancreatic ductal adenocarcinoma (PDA). Recruitment and activation of γδT cells was contingent on diverse chemokine signals. Deletion, depletion, or blockade of γδT cell recruitment was protective against PDA and resulted in increased infiltration, activation, and Th1 polarization of αβT cells. Although αβT cells were dispensable to outcome in PDA, they became indispensable mediators of tumor protection upon γδT cell ablation. PDA-infiltrating γδT cells expressed high levels of exhaustion ligands and thereby negated adaptive anti-tumor immunity. Blockade of PD-L1 in γδT cells enhanced CD4+ and CD8+ T cell infiltration and immunogenicity and induced tumor protection suggesting that γδT cells are critical sources of immune-suppressive checkpoint ligands in PDA. We describe γδT cells as central regulators of effector T cell activation in cancer via novel cross-talk. [Display omitted] •γδT cells are highly prevalent in human pancreatic carcinoma•Deletion or interruption of γδT cell recruitment is protective in pancreatic cancer•Pancreatic cancer infiltrating γδT cells express high levels of checkpoint ligands•γδT cells disable αβT cell activation via checkpoint receptor ligation γδT cells are key regulators of effector T cell activation in pancreatic cancer and a new target for cancer immunotherapy.